Efek Inokulasi Cendawan Mikoriza Arbuskular Indigen dan Dosis Mulsa Terhadap Keefektifan Mikoriza dan Karakteristik Agronomi Padi Gogo (Oryza sativa L.) di Rumah Kaca - Kuswanta Futas Hidayat (Jurnal Agrista, 2008)
Effect Inoculation of Indigenous Population of Arbuscular Mycorrhiza Fungi and Dosage of Mulch on Mycorrhiza Effectiveness and Agronomy Characteristics of Upland Rice (Oryza sativa L.) in Green HouseABSTRACT. The experiment was conducted to study agronomy characteristics and mycorrhiza effectiveness of upland rice in green house with various levels of AMF inoculants and mulch dosage application. The pot of experiment was carried out in the green house of Agricultural Faculty, The University of Lampung from October 2004 untill February 2005. The experiment used randomized complit block design arranged in factorial pattern with two factors. The first factor was dosages of mulch (0, 5, 10, and 15 ton ha-1) and the second factor was AMF inoculants dosages which consist of four levels, those were 0, 25, 50, and 75 g pot-1. The result of this experiment showed that dosages of mulch and AMF inoculants affect to agronomy characteristics and mycorrhiza effectiveness of upland rice in the green house. Up to the certain dosages, inoculants of AMF and mulch raised P content in plant, shoot dry weight, root dry weight, harvest index, and mycorrhiza effectiveness.